What is the analgesic range of acupuncture stimulus for treating acute pain? - Choi, Kwang-Ho; Cho, Seong Jin; Kim, Minji; Kwon, O Sang; Kang, Suk-Yun; Seo, Su Yeon; Bang, Se Kyun; Ryu, Yeonhee (Frontiers in Human Neuroscience, 2023)
Since the analgesic effect of acupuncture stimulation is derived from different mechanisms depending on the type of pain, it is important to know which acupuncture points to stimulate. In this study, to confirm the effect of acupuncture stimulation on acute pain from a neurological point of view, somatosensory evoked potential and sensory threshold changes were evaluated to identify the nerve range that is affected by acupuncture stimulation on LI4 (Hapgok acupuncture point, of the radial nerve) during acute pain. The subjects were 40 healthy men and women aged 19-35 years. The study was designed as a randomly controlled, crossover trial with acupuncture stimulation at LI4 as the intervention. The washout period for acupuncture stimulation was 2 weeks, and the subjects were divided into two groups, i.e., an acupuncture stimulation group and a non-stimulation group, with 10 men and 10 women in each group. somatosensory evoked potential measurement was carried out for 5 minutes by alternately applying 2 HZ-pulse electrical stimulation to the thumb and the little finger of the hand acupunctured with a 64-channel electroencephalogram. The verbal rating scale was used before and after each acupuncture stimulation session. The results of the study confirmed that the somatosensory evoked potential amplitude value of the thumb was significantly decreased and that the intensity of sensory stimulation corresponding to a verbal rating scale score of 6 was significantly increased only in the thumb after acupuncture stimulation. Therefore, the results show that acupuncture treatment for acute pain is more effective when direct acupuncture stimulation is applied to the painful area.